Сіроглиняна кераміка Нижнього Подніпров’я 1 ст. до н. е. — 2 ст. н. е. - Никоненко, Д.Д. (Археологія, 2017)
У статті висвітлюється комплекс сіроглиняної кераміки з пізньоскіфських городищ і могильників Нижнього Дніпра та доводиться її ольвійське походження. Окремо розглянуто актуальні проблеми дослідження цієї групи посуду та способи їх вирішення шляхом використання сучасних міждисциплінарних методів дослідження. The article is devoted to the assemblage of gray-clay pottery tableware from the Late Scythian hill-forts and burial mounds of the Dnipro River lower region. Pottery of this group is found in all layers of the Ancient Greek sites at the north coast of the Black Sea, at the Late Scythian monuments of the Dnipro and the Danube Rivers lower regions and in the Crimea; later it becomes a peculiar feature of Cherniakhiv culture. The above analysis of materials indicates imported nature of gray pottery in «Minor Scythia» of the Dnipro River lower region. Multiple analogies can allow determining Olbia as the main direction of such imports. Ancient Greek forms known in Olbia back in the pre-Getian period predominate in the assemblage of the Late Scythian gray-clay pottery. Статья посвящена характеристике комплекса сероглиняной гончарной столовой посуды позднескифских городищ и могильников Нижнего Поднепровья. Керамика этой группы встречается во всех слоях античных памятников Северного Причерноморья, на позднескифских памятниках Нижнего Днепра, Нижнего Дуная и Крыма, а позднее становится характерным признаком черняховской культуры. Проведенный анализ материалов указывает на импортный характер серойке рамики нижнеднепровской «Малой Скифии». Множественные аналогии позволяют определить Ольвию, как основное направление данного импорта. В составе комплекса позднескифской сероглиняной керамики доминируют античные формы, известные в Ольвии еще в догетский период.